1883 Mich. Pub. Acts, No. 138, § 1. - (:unkn) unknown (General Publisher, 1883)
That no person shall sell, give, or furnish to any child under the age of thirteen years, any cartridge of any form or material, or any pistol, gun, or other mechanical contrivance, specially arranged or designated for the explosion of the same.
--
Keywords: TRANSFER - MINORS